The Deceptive Fermata of HIV-Criminalization Law: Rereading the Case of “Tiger Mandingo” Through the Juridico-Affective - Lawless, Joseph F. (Columbia Journal of Gender and Law, 2017)
In July 2015, Michael Johnson, a twenty-three-year-old Black queer college student in Missouri, was sentenced to slightly over thirty years in prison on one count of reckless transmission of Human Immunodeficiency Virus (HIV) to another person and on four counts of reckless attempted transmission of HIV. Johnson’s conviction and exorbitant carceral sentence are not unique, however. State penal laws criminalizing the transmission of HIV have existed for well over twenty-five years and have remained nearly impervious to legal challenge throughout that time. This Article queries the continued vitality of HIV-criminalization laws and argues that their survival reflects their investment in appeals to the affective—the sensations of bodily impingement and intrusion that the terrifying spectacle of HIV is meant to conjure. The injection of the affective into the jurisprudential regime of HIV criminalization is shown to be at the core of Michael Johnson’s prosecution and conviction, animating Johnson’s unwitting transformation into HIV itself. Reflecting on this disturbing genealogy, the discussion concludes with both legal and critical prescriptions to combat the persistence of HIV stigma.